The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1073/pnas.0801360105
|View full text |Cite
|
Sign up to set email alerts
|

Late-surviving megafauna in Tasmania, Australia, implicate human involvement in their extinction

Abstract: Establishing the cause of past extinctions is critical if we are to understand better what might trigger future occurrences and how to prevent them. The mechanisms of continental late Pleistocene megafaunal extinction, however, are still fiercely contested. Potential factors contributing to their demise include climatic change, human impact, or some combination. On the Australian mainland, 90% of the megafauna became extinct by Ϸ46 thousand years (ka) ago, soon after the first archaeological evidence for human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 30 publications
1
76
0
Order By: Relevance
“…The case for a human role was buttressed by claims that MIS3 (60-28 ka) was a time of relatively stable climatic conditions (13). As such, human activities were therefore the only credible explanation for the extinctions (2,11,38).…”
Section: Human-mediated Extinction Processesmentioning
confidence: 99%
“…The case for a human role was buttressed by claims that MIS3 (60-28 ka) was a time of relatively stable climatic conditions (13). As such, human activities were therefore the only credible explanation for the extinctions (2,11,38).…”
Section: Human-mediated Extinction Processesmentioning
confidence: 99%
“…Similar conclusions were drawn from an OSL study undertaken by Roberts and colleagues (2001) at Cuddie Springs, in which multiple age populations were identified in the single-grain OSL data, and the authors subsequently concluded the site to have significant sediment disturbance. A similar pattern of multiple age populations was determined for a Tasmanian study of megafauna (Turney et al [2008] and discussion in Cosgrove et al [2010Cosgrove et al [ : p. 2497); however, some of these age populations were "omitted for clarity," and an age of~45 Ka was used instead. While further work is needed to better standardize the treatment of OSL data, there is still much that can be learned from the sites mentioned earlier.…”
Section: Site Setting and Paleoenvironmental Historymentioning
confidence: 99%
“…A series of recent studies restricted to specimens and sites dated with high confidence suggest that the extinctions were concentrated between 50 and 40 ka on mainland Australia [24,26,[33][34][35][36], and slightly later in Tasmania [37]. On the other hand, more extensive compilations of occurrences in the fossil record, lacking controls on date quality, suggest staggered extinction through the period from 400 to about 20 ka [6].…”
Section: Chronology Of Megafaunal Extinctionmentioning
confidence: 99%